Strengthening Community Health Workers’ Capacity for Non-Communicable Disease Prevention and Control in Rural Settings: A Participatory Action Research Protocol - Muhamad Zulfatul A'la; Rondhianto Rondhianto; Ridlwan Kamaluddin; Pairin Yodsuban (Fakultas Ilmu-ilmu Kesehatan, 2026)
Non-communicable diseases (NCDs) are a leading cause of mortality and morbidity worldwide. Strengthening the capacity Community Health Workers (CHWs) is a key strategy for improving NCD prevention and control. However, its implementation remains suboptimal, particularly in rural settings. This study aims to co-design, implement, and refine a CHW capacity-building intervention for NCD prevention and control in rural settings using a Participatory Action Research (PAR) approach. This protocol describes a qualitative PAR study with process evaluation from August 2024 to June 2026 at Kaliwates Public Health Center (PHC), Jember, Indonesia. The completed pre-PAR phase involved 20 participants (CHWs and healthcare providers) to identify baseline needs and intervention development, while the subsequent PAR phase will involve 15 purposively selected CHWs. The post-PAR phase will explore participants' experiences, perceived benefits, feasibility, and sustainability of the co-developed intervention through observations, in-depth interviews, the Delphi method, and focus group discussions (FGDs). Data from the completed pre-PAR phase were analyzed using thematic analysis and Multiple-Perspective Interviews (MPI), supported by ATLAS.ti software, whereas data from the PAR and post-PAR phase will be analyzed upon completion. Ethical approval was obtained before the commencement of the pre-PAR phase. Preliminary findings from the pre-PAR needs assessment identified three overarching themes: systemic barriers to CHW role fulfilment; capacity gaps in training and skill development; and the need for participatory, culturally embedded training approaches. These findings provide an empirical foundation for the co-design, implementation, and evaluation of a contextually relevant CHW capacity-building intervention for NCD prevention and control in rural settings.